Vagus Nerve Stimulation for Intractable Seizures in Children: the University of Puerto Rico Experience - Pastrana, Emil A; Estronza, Samuel; Sosa, Ivan J. (Puerto Rico Health Sciences Journal, 2011)
Objective: Vagus nerve stimulation (VNS) is considered an alternative treatment for patients with medically refractory epilepsy who are not candidates for resective surgery. It consists of intermittent electrical stimulation of the left vagus nerve in the neck. Such stimulation has been demonstrated to be efficacious, safe, and well tolerated, offering these patients another option for seizure control. The aim of this study was to evaluate the experience of VNS at the University of Puerto Rico, and to examine demographic data, types of seizures, and seizure-control outcomes among treated subjects. This study is the first account of VNS in a pediatric population living in the Caribbean area. Methods: A retrospective analysis of 13 patients treated at the University Pediatric Hospital in San Juan, Puerto Rico, was undertaken. Different types of seizures were identified and managed. Results: The mean age at implantation was 12 years; 77% of patients were female. The most common type of seizure treated was generalized tonic-clonic (24%), followed by complex partial (23%). Sixty-nine percent of patients demonstrated a reduction in monthly seizure frequency. Ninety-three percent of caregivers reported improvements in alertness and communication. Conclusion: Vagus nerve stimulation is a safe and effective way to treat medically refractory epilepsy and should be considered as a non-pharmacological treatment for select patients with medically refractory epilepsy.